IMPLEMENTATION OF THE PRINCIPLES OF ACADEMIC INTEGRITY IN HIGHER EDUCATION INSTITUTIONS OF UKRAINE - Bashkir, Olha (Educological discourse, 2021)
Taking into account the current state of development of higher education and science, the peculiarities of the introduction of the principles of academic integrity in the structure of higher education institutions are indicated in the study. The essence of the concept of academic integrity was clarified basing on the study of normative documents and regulations (Law of Ukraine on Education and Law of Ukraine on Higher Education), recommendations for higher education institutions on the development and implementation of a university system of academic integrity, approved by the National Agency for Quality Assurance in Higher Education. Main vocation of academic integrity, its features of compliance and application in educational and scientific activities of all participants in the educational process are revealed in the study. On the example of H.S. Skovoroda Kharkiv National Pedagogical University it was found that higher education institutions, guided by the above laws and recommendations, operates on their own principles of academic integrity in view of the peculiarities of the free economic zone, its specifics, areas of training future professionals and scientific activities. An example of a university system for ensuring the principles of academic integrity and ethics of academic relations is revealed, which consists of five components: regulatory framework, information base, structural units and authorized commissions, tools for implementation and control. It is noted about the creation of such a system on the basis of the recommendations for higher education institutions on the development and implementation of the university system of academic integrity, approved by the decision of the National Agency for Quality Assurance in Higher Education. The activity of separate structural links of the educational institution on realization of the principles of academic integrity is analyzed. A number of promising ways to implement the principles of academic integrity in higher education institutions is proposed. Among them are the development of normative documents of the Free Economic Zone, information materials, banners, methodical instructions, preparation of videos, holding popular science events, etc.